Comprehensive haccp strategies for reducing incidence of food poisoning (salmonella prevalence) in ready-to-eat-broiler chicken - Ndife, Joel; Egege, S.C.; Komolafe, G.O. (Global Journal of Food and Agribusiness Management, 2011)
In order to reduce the prevalence of SALMONELLA on ready-to-eat chicken, a number of approaches have proven useful, as there is no one stop solution available in practice. The use of the HACCP (Hazard Analysis Critical Control point) approach, based on the use of multi-functional strategies which combine the innovative use of sanitizers and modern disinfection techniques supervised by professional food handlers and food regulators with a visionary commitment by management from the production, through the processing, preservation, handling and final preparatory stages, will surely help to eliminate or reduce significantly the prevalence of salmonella and the consequent food poisoning effects in the society